Poética e poesia de Nuno Júdice nos anos 1970: as dimensões formadoras do corpo errante do poeta - Guedes, Juliana Braga (2024)
Generally, an author is often discussed by encompassing their most well-known texts. There's even a tendency to analyze the writer's craft in their mature phase. Moreover, when presenting works that span different genres, scholars tend to focus on author’s narrative works. However,, this dissertation studies the beginnings and the lyrical genre as well. It examines the early poetry works of Portuguese poet Nuno Júdice, highlighting initial literary activity not just any beginning. It occurs in the 1970s in Portugal, a peculiar period for Portuguese nation that not only alters the country's history, but also local poetry scene. This work primarily analyzes three dimensions identified as recurring lines of thought in Nuno Júdice: narrativity, painting, and landscape, which contributed to the formation of a sui generis body qualified as errant. Contrary to the standard biological functions of a human body, embodiment of the lusitanian writer begins to conceive a new use, deviating from any consensual purpose. The methodology aimed to scrutinize each of the poet's poetry works published in the 1970s, alongside with reviews and essays by commentators of that time published in Portuguese periodicals and newspapers. Subsequently, articles, theses, and dissertations by later scholars that partly considered the early works of the Portuguese writer were collected. Although these works showed a greater preference for the author's poetics from the 1980s onwards. Following this, the constant themes in Júdice's poems were collected, pointing to the mentioned attributes of narrativity, painting, and landscape. These categories established the construction of a dark and emancipated body from its physicochemical functions. As results, narrativity was observed through storytelling within the poem's space, noting the presence of dialogical relationships focusing on intertextuality. Painting gave rise to developments in the ekphrastic process, examining convergences and frictions between the Portuguese author's poetic texts and the paintings that aided him in artistic-verbal creation. The landscape explored phenomenological thinking around the elements of devastation found in the poems. Lastly, the errant body remained aligned with the phenomenological perspective and provided a new viewpoint on the theme of embodiment, standing apart, for example, from the usual trend of eroticism. Finally, it was noted that today's readers seem less interested in the intense fluidity of Nuno Júdice's poetic universe due to the instant consumption of poetry in the digital age promoted by social media. For a reading of this Portuguese poet's unique world, it is important to focus on the small pieces presented by the poetic voices. The narrative images presented in judicean poems only annoy the inattentive or lazy reader, who often finishes reading the poem, sees nothing in it, and leaves aside the hermeneutic exercise of human learning from lyrical expression.